(untitled) (Південний архів (історичні науки), 2024)
The purpose of the research is to introduce new sources for studying the Jewish history and the history of the municipal self-government of Kherson in the early 20th century into scientific discourse. The document presented in this article is a full-text copy of the personal opinion of the Governor of Kherson Gubernia on modernizing the port in 1908. This source was previously kept in F.1. The Office of Kherson Governor of the State Achieve in Kherson region. The methodological foundation includes scientific methods of analysis, synthesis, and archaeological methods in accordance with the rules of publishing tests in the late 19th – early 20th centuries. The main research results. The central part of the published source is occupied by the personal opinion of the Governor of Kherson Gubernia, Bantysh Fedir Oleksandrovych, on modernizing the port of Kherson in the early 20th century. The municipal government dealt with this issue, and the governor did not like the ideas and the content of their actions in the process of implementation. In his opinion, the municipal self-government did not modernize the port efficiently since Kherson’s trading operations depended on Mykolaiv and Odesa. His investigation allowed him to find out that the municipal self-government of Kherson was run from the outside by Jews who had business interests with major Odesa financiers of that time. Responding to this situation, the Governor conveyed his ideas in several letters to the central government, explaining that the most successful idea would be to modernize the port in a different direction, which would facilitate the delivery of commodities and bread from the left bank of the Dnipro and, as a result, would increase the role of Kherson port and help it win the competition with Oleksandrivsk and Mykolaiv. Overall, Bantysh F. O. had a negative impression of the actions of the municipal selfgovernment, as he saw that it was completely under the influence of the group managed by the influential and wealth Jew Moses Semenovych Rabinovich. Therefore, the pages of this document depict an authentic living history of the city of Kherson, which allows an understanding of who really governed the city. In addition, the document is full of statistical data and references to other documents that have not survived and presents a detailed picture of relationships between the authorities at different levels: central, regional, and municipal.